2013
DOI: 10.1039/c3ta01169k
|View full text |Cite
|
Sign up to set email alerts
|

A novel polymer electrolyte to improve the cycle life of high performance lithium–sulfur batteries

Abstract: A novel polymer electrolyte was proposed for lithium-sulfur batteries. A functional poly(methyl methacrylate) containing inorganic trimethoxysilane domains was synthesized and blended with poly(vinylidenefluoride-co-hexafluoropropylene) to modify the morphology of the polymer electrolyte, resulting in superior performance of the lithium-sulfur battery cell in terms of delivering high discharge capacity and stable cyclability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 15 publications
1
57
0
Order By: Relevance
“…[ 30 ] In spite of their instability with the presence of polysulfi de anions, carbonate-based electrolytes have proven to be safe with cathode composites in which sulfur was either physically confi ned within micro-sized pores of a carbon structure, which avoided polysulfi de dissolution to the electrolyte, or covalently immobilized in polymeric composites. [ 38,46,165,170,177,[179][180][181] For example, Wang et al demonstrated this effect with sulfur in a microporous-mesoporous carbon material, [ 46 ] and Xin et al did the same with metastable small sulfur molecules of S 2-4 in a microporous carbon matrix. [ 38 ] At present, the preferred ether solvents in Li-S cells are dimethyl ether (DME), [ 24,72,161 ] tetra(ethylene glycol) dimethyl ether (TEGDME), [ 70,72,80,123,169 ] polyethylene glycol dimethyl ether (PEGDME), and 1,3-dioxolane (DOL), [ 69,85,161,171,[182][183][184] with lithium bis(trifl uoromethanesulfonyl)imide (LiTFSI) as the Li + ion carrier.…”
Section: Solvents' Impact On the Dissolved Polysulfi De Speciesmentioning
confidence: 96%
See 1 more Smart Citation
“…[ 30 ] In spite of their instability with the presence of polysulfi de anions, carbonate-based electrolytes have proven to be safe with cathode composites in which sulfur was either physically confi ned within micro-sized pores of a carbon structure, which avoided polysulfi de dissolution to the electrolyte, or covalently immobilized in polymeric composites. [ 38,46,165,170,177,[179][180][181] For example, Wang et al demonstrated this effect with sulfur in a microporous-mesoporous carbon material, [ 46 ] and Xin et al did the same with metastable small sulfur molecules of S 2-4 in a microporous carbon matrix. [ 38 ] At present, the preferred ether solvents in Li-S cells are dimethyl ether (DME), [ 24,72,161 ] tetra(ethylene glycol) dimethyl ether (TEGDME), [ 70,72,80,123,169 ] polyethylene glycol dimethyl ether (PEGDME), and 1,3-dioxolane (DOL), [ 69,85,161,171,[182][183][184] with lithium bis(trifl uoromethanesulfonyl)imide (LiTFSI) as the Li + ion carrier.…”
Section: Solvents' Impact On the Dissolved Polysulfi De Speciesmentioning
confidence: 96%
“…[ 5,7,74,80,168,169 ] However, because ethers have issues associated with the severe polysulfi de dissolution, along with a low boiling point that may cause safety problems in commercial applications, researchers have been testing less volatile, more viscous electrolytes with lower polysulfi de solubility, such as sulfone-based electrolytes, ionic liquid-based electrolytes, and polymer and solid state electrolytes. [ 73,92,170,171 ] Other solvents intended to suppress the solubility/mobility of lithium polysulfi de yet maintain a high lithium-ion conductivity include glyme-Li salt complexes and partially fl uorinated ethers. [ 139,167,[172][173][174][175][176] Advanced characterization techniques have played an important role in assessing the stability of solvents with the presence of the highly reactive polysulfi de species and discovering depletion mechanisms.…”
Section: Solvents' Impact On the Dissolved Polysulfi De Speciesmentioning
confidence: 99%
“…[ 26,28,55 ] Combining PVdF-HFP, poly(methyl methacrylate) (PMMA) with inorganic trimethoxysilane, mesoporous silica (MPS), or montmorillonite nanoclay (MMT), Chen and co-workers reported a series of polymer (gel) electrolytes to enhance the performances of pPAN@S composites. [56][57][58] Gel electrolytes with nano inorganic particles provide stable ionic conductivity and possibly also modify the interfacial properties of the electrochemical system, including the interface between the electrolyte and the lithium anode. A gel electrolyte with a polymer matrix composed of PVdF-HFP/PMMA/5 wt% MMT showed an ionic conductivity of [ 38 ] and rate performances (E) [ 38 ] of 3D pPAN@S/GNS.…”
Section: Research Newsmentioning
confidence: 99%
“…Different kinds of solid electrolytes, including polymer electrolytes [1,[116][117][118], thio-LISICON electrolytes [119], and Li 2 S/P 2 S 5 -based electrolytes [120,121], have been widely studied for all-solid rechargeable lithium batteries. In this section, we will discuss and highlight most recent breakthroughs in solid electrolytes for all-solid Li-S cells, including polymer electrolytes and non-polymer electrolytes.…”
Section: Solid Electrolytesmentioning
confidence: 99%